Pengaruh Harga, Promosi dan Inovasi Terhadap Kepuasan Pelanggan Provider Telkomsel Pada Generasi Milenial Muslim di Kota Bekasi - Muhammad Richo Rianto; Novita Wahyu Setyawati; Heni Rohaeni; Dewi Sri Woelandari (ITB AAS INDONESIA Surakarta, 2022)
This study was used to measure the effect of price, promotion and product innovation on customer satisfaction Telkomsel provider in the millennial generation in Bekasi City. This research is a quantitative study in which the object used is the millennial generation in Bekasi City. This research was conducted using a non-probability sampling technique with a purposive sampling method. The number of samples used in this study were 181 respondents. The design used in this research is hypothesis testing using the structural equitation model (SEM) – SmartPLS 3.0 The results of this study provide an explanation that the variables of price, promotion, and product innovation have a positive effect on customer satisfaction in the millennial generation in Bekasi City.This research has a limited object of research which is only carried out on the millennial generation in Bekasi City. This is used as a suggestion for future researchers. The novelty in this study combines the variables of price, promotion and product innovation on customer satisfaction in the millennial generation in Bekasi City.